Urban Development and Rural Poverty in Java: A Challenge for Decentralized Local Government - Wilmar Salim (The Institute for Research and Community Services, Institut Teknologi Bandung, 2005)
The Government of Indonesia has pursued the strategy of dispersed development to address the issue of environmental degradation, to reduce the concentration of development in one major center, in order to achieve a sustainable urban form. The effectiveness of this strategy is being questioned, since the